Integration of Local Culture in the Search, Solve, Create and Share (SSCS) Learning Model to Improve Scientific Literacy: A Literature Review - Listia, Amanda Putri; Wijayanti, Astuti; Ernawati, Tias; Septiani, Devi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
Scientific literacy is an essential competency for students in the 21st century, yet its development in Indonesia remains a challenge. One of the contributing factors is the lack of contextual learning models that connect scientific concepts with students' daily lives. This study explores the integration of local culture into the Search, Solve, Create, and Share (SSCS) learning model as a potential approach to improving students' scientific literacy. A Systematic Literature Review (SLR) was conducted by analysing relevant studies published between 2021 and 2024 in Sinta 1, Sinta 2, and ERIC databases. The articles were selected based on predefined inclusion and exclusion criteria and analysed using thematic analysis. The findings indicate that while science literacy and local culture have been widely discussed separately, research explicitly integrating the SSCS model with local culture remains limited. The results highlight the potential of this integration in enhancing students' engagement and conceptual understanding while addressing challenges in its implementation. This study provides recommendations for developing contextual and culturally relevant science education, which not only fosters scientific literacy but also contributes to the preservation of local wisdom.